3D Thermal Analysis for CFETR Pre-Superheated Water-Cooled Blanket. (17th November 2017) - Khodak, A.; Titus, P.; Brown, T.; Klabacha, J.; Nielsen, H.; Cheng, X.; Liu, S.
Abstract: Initial China Fusion Engineering Test Reactor (CFETR), blanket design, includes water-cooled ceramic breeder (WCCB) blanket operating in pre-superheated regime. This condition allows efficient cooling; however it requires accurate control and analysis to avoid zones with excessive heat flux. Analysis of the coolant flow and heat transfer in CFETR Pre-Superheated Blanket was performed using ANSYS CFX and included: 3D coolant flow analysis, external volumetric and surface heating effect, and two-phase wall boiling. ASIPP CAD Model imported directly into ANSYS Workbench Design Modeler as a STEP file. Fluid volume is created using Design Modeler Fill operation, and converting Inlet and Outlet surfaces. Meshing was performed using CFX method available within the framework of the ANSYS mesh generator. Application of tetrahedral elements for meshing of the internal regions allowed automatic mesh generation. Advanced sizing functions were used with automatic mesh inflation depending on wall proximity and curvature. Conjugated heat transfer analysis was performed including solution of heat transfer equations in solid and liquid parts, and solution of the flow equations in the liquid parts. Coolant flow in that was assumed turbulent and was resolved using Reynolds averaged Navier-Stokes equations with Shear Stress Transport turbulence model. RPI model for wall driven boiling is used. Inhomogeneous two-phase flow is resolved solving two sets of momentum and energy equations for liquid and steam. Results showed ability of the model to simulate two-phase boiling flow in complex configuration.